1999
DOI: 10.1002/(sici)1097-4652(199902)178:2<121::aid-jcp1>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

ETS-1 converts endothelial cells to the angiogenic phenotype by inducing the expression of matrix metalloproteinases and integrin ?3

Abstract: The transcription factor ETS-1 is induced in endothelial cells (ECs) by angiogenic growth factors and the specific elimination of ETS-1 synthesis by antisense oligodeoxynucleotide inhibited angiogenesis in vitro (Iwasaka et al., 1996, J Cell Physiol 169:522-531). To understand the precise role of ETS-1 in angiogenesis, we established both high and low ETS-1 expression EC lines and compared angiogenic properties of these cell lines with those of the parental murine EC line, MSS-31. Although growth rate was alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(112 citation statements)
references
References 43 publications
5
105
0
2
Order By: Relevance
“…This was unexpected since previous studies on the e ects of Ets1 over-expression on cell proliferation in vitro had yielded contradictory results, probably due to di erences in species origin between Ets1 and the cells used (Seth and Papas, 1990;Suzuki et al, 1995) but none had reported an e ect on cell density at con¯uence. The sole report describing the overexpression of mouse Ets1 in endothelial cells derived from mouse spleen showed no di erences in cell growth or apoptosis, nor in the morphology of the cells (Oda et al, 1999). This, added to our results, suggests that the decrease in cell density at con¯uence induced by mouse Ets1 could be restricted to brain capillary endothelial cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This was unexpected since previous studies on the e ects of Ets1 over-expression on cell proliferation in vitro had yielded contradictory results, probably due to di erences in species origin between Ets1 and the cells used (Seth and Papas, 1990;Suzuki et al, 1995) but none had reported an e ect on cell density at con¯uence. The sole report describing the overexpression of mouse Ets1 in endothelial cells derived from mouse spleen showed no di erences in cell growth or apoptosis, nor in the morphology of the cells (Oda et al, 1999). This, added to our results, suggests that the decrease in cell density at con¯uence induced by mouse Ets1 could be restricted to brain capillary endothelial cells.…”
Section: Discussionsupporting
confidence: 67%
“…Chicken Ets1 induces the expression of Ets1 (Seth and Papas, 1990) and Egr1 (Robinson et al, 1997) in mouse 3T3 stable transfectants. In mouse MSS-31 endothelial cells, murine Ets1 increases the mRNA levels of angiogenesis-related molecules such as MMP-1, -3, -9 and the b3 integrin sub-unit (Oda et al, 1999). Identi®cation of Ets1 target genes in endothelial cells remains an important issue for understanding the role of this factor in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This is a consequence of the prevalence of proangiogenic factors compared to the antiangiogenic ones. We demonstrated by means of RT -PCR and Northern blotting that pancreatic and colon adenocarcinoma cells express various angiogenic factors like the endothelial cell mitogens-VEGF and bFGF, ETS-1 (documented as an angiogenic factor by Oda et al, 1999a), as well as haemoxygenase 1 (unpublished data), which has been recently found to induce angiogenesis (Deramaudt et al, 1998). The presence of these factors is likely to mediate the growth and invasion of these adenocarcinomas by induction of angiogenesis.…”
Section: Discussionmentioning
confidence: 83%
“…To date, 23 different human MMPs have been identified (Somerville et al, 2003). Endothelial cells are reported to express MMP 1, MMP 2, MMP 3 and MMP 9 (Oda et al, 1999;Hummel et al, 2001), and the expression of MMP 3 can be induced by the angiogenic growth factor FGF B (Pintucci et al, 2003).…”
Section: Discussionmentioning
confidence: 99%